Introducing the Motivation, Methodology, and Research Prospects - Andy Buschmann (Journal of Current Southeast Asian Affairs, 2018)
This article presents the Myanmar Protest Event Dataset , a unique dataset on protest assemblies in transitional Myanmar/Burma. The data contents were derived from the most visible forms of assembly – demonstrations, protest marches and labour strikes – and collected through a protest event analysis of local news reports. The coded variables range from information on the actual moment of the protest event, such as participants, issue, duration and location, to the aftermath, including variables related to legal consequences for protesters and the success of protesters’ claims, and many others. Besides a concise description of the research design and data collection process, this article discusses methodological strengths and weaknesses of the dataset.